Developing cross-cultural measurement - Tran, Thanh V. (Oxford : Oxford University Press, 2009)
This volume guides social work researchers in developing and assessing cross-cultural research measurements. The chapters illustrate how to formulate research questions, select observable indicators, understand cross-cultural translation evaluate measurement equivalence, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social work with minorities -- United States -- Methodology; Cultural awareness -- United States -- Methodology